ChemInform Abstract: Polycyclic Tetrahydroxanthones from Streptomyces chrestomyceticus BCC 24770. Issue 21 (6th May 2016) - Bunyapaiboonsri, Taridaporn; Lapanun, Sanisa; Supothina, Sumalee; Rachtawee, Pranee; Chunhametha, Suwanee; Suriyachadkun, Chanwit; Boonruangprapa, Tanapong; Auncharoen, Patchanee; Chutrakul, Chanikul; Vichai, Vanicha
Abstract: Chrestoxanthone A (Ia) shows antifungal activity against Curvularia lunata and Alternaria brassicicola.